Non-steroidal anti-inflammatory drugs induced toxic epidermal necrolysis - Samudrala, Lahari; Singh, Bhanu Pratap; Papasani, Rajya Laxmi; Bashaboina, Tharun; Tadikonda , Ramarao (International Journal Of Community Medicine And Public Health, 2025)
This case report presents a 48-year-old woman with a history of chronic kidney disease who experienced toxic epidermal necrolysis (TEN), also known as Lyell's syndrome, an uncommon and severe adverse drug reaction. The TEN was attributed to the use of non-steroidal anti-inflammatory drugs (NSAIDs). Cutaneous involvement exceeded 80% of the body surface area (BSA), encompassing ocular, oral, and nasal mucosa, as well as the trunk, bilateral limbs, and genitalia. Treatment commenced with aggressive fluid resuscitation, the administration of cyclosporine, and meticulous dermal care. The patient was ultimately discharged following approximately one month of intensive therapy.